Trocas gasosas e indicadores de crescimento de milho e plantas daninhas em situação de competição e deficit hídrico - Freitas, Claudia Daianny Melo (2018)
Soil water deficit has been an increasingly frequent situation in dry crops in Brazil and may have the consequence of reducing crop growth and production. This situation can be further aggravated by the occurrence of weeds and the establishment of competition for growth resources such as water. The understanding of the factors related to this interaction can contribute to the elaboration of management strategies. Thus, the effects of water stress was evaluated and competition on physiological components of corn and weed growth, and Urochloa decumbens (Stapf) and R.D. Webster Bidens pilosa L. The experiment was performed in 5 x 2 factorial arrangement, distributed in a randomized block design with eight repetitions, with the first factor corresponding to the arrangements among species (corn + U. decumbens, corn + B. pilosa, corn, U. decumbens and B. pilosa without competition), and the second factor to two water regimes (with and without water deficit) The water deficit was established in the V3 stage of corn and lasted five days, until the photosynthetic rate of the crop reached values close to zero, at which time irrigation was resumed. The plants were submitted to the following evaluations: stomatal conductance (gs; μmol H2O m-2 s-1), transpiration (E; mmol H20 m-2 s-1) and liquid photosynthetic rate A; μmol CO2 m-2), performed daily until the CO2 assimilation rates of the plants submitted to the water deficit were similar to those of the irrigated ones. At the end of the experiment were evaluated: plant height, leaf area, specific leaf area (ratio between leaf dry matter per leaf area), shoot dry matter, root dry matter and total dry matter (g). The water deficit reduced the gs, E and A of isolated or competing corn plants. However its effect was intensified when coexistence with the U. decumbens, compared to the B. pilosa. In the plants of U. decumbens the water deficit reduced to gs and E, whereas B. pilosa reduced only to E. The water restriction condition for five days reduced A of the weeds when in competition, but did not change in isolated cultivation. The temporary water deficit in the soil reduced the growth of corn plants, but did not affect the U. decumbens and B. pilosa plants. The competition reduced the growth of corn and U. decumbens plants. Corn in competition with U. decumbens in deficit showed the greatest reduction of total dry matter in relation to the other treatments. Competition may intensify the negative effects caused by soil water deficit in corn and U. decumbens plants.